A method for preparing pressureless sintered silicon carbide ceramic large plates by low deformation gel casting

By modifying silicon carbide powder and controlling slurry components, combined with gypsum board fixation and constant temperature and humidity drying technology, the cracks and deformation problems of large silicon carbide ceramic plates in gel injection molding are solved, and the drying performance of the finished product is improved and strength, achieving high density and high hardness sintering effect.

CN118619680BActive Publication Date: 2024-12-20NANTONG SANZER PRECISION CERAMICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411087329.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-20
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Gel injection molding often presents microcracks and deformations when preparing large silicon carbide ceramic plates, resulting in low yields and it is difficult for the prior art to effectively solve this problem.

Method used

By modifying silicon carbide powder and controlling the slurry components, high solid content and low viscosity silicon carbide ceramic slurry are prepared, and gypsum board is used to fix the blank during the preliminary drying process, and water is slowly discharged through capillary force. Increase the strength of the blank to resist drying stress and reduce the occurrence of cracks and deformation.

Benefits of technology

The drying performance and strength of the large silicon carbide ceramic plate is significantly improved, cracks and deformation are reduced, and high density and high hardness of the large silicon carbide ceramic plate is obtained.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a method for preparing pressureless sintered silicon carbide ceramic slabs by gel injection molding with low deformation, and relates to the field of ceramic technology, comprising the following steps: preparing slurry, ball milling the slurry, degassing after ball milling, vibrating during degassing, and obtaining degassing slurry; adding catalyst and initiator to the degassing slurry, pouring into a mold after stirring, and obtaining a green body after forming and curing, clamping and fixing the green body with a gypsum board and letting it stand for preliminary drying at constant temperature and humidity; after standing, the gypsum board is removed, and the green body is dried according to a drying system to obtain a dried green body, and the dried green body is pressurelessly sintered according to a sintering system to obtain a silicon carbide ceramic slab. The present application has the effect of improving the strength and drying performance of the green body, can reduce the occurrence of microcracks and deformation, and improve the density and hardness of the ceramic slab.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramic technology, and in particular to a method for preparing a large pressureless sintered silicon carbide ceramic plate by gel injection molding with low deformation. Background Art

[0002] Silicon carbide ceramics not only have excellent room temperature mechanical properties, such as high bending strength, excellent oxidation resistance, good corrosion resistance, high wear resistance and low friction coefficient, but also have the best high temperature mechanical properties such as strength and creep resistance among known ceramic materials. Silicon carbide ceramic materials sintered by hot pressing, pressureless sintering and hot isostatic pressing can still maintain good high temperature strength at 1600℃, and are the best high temperature strength materials among ceramic materials. Therefore, its products are widely used in the heating and heat exchange industry.

[0003] In recent years, new colloidal molding technologies such as filter press molding, gel casting molding and direct solidification molding and other in-situ curing methods can be used to prepare high-reliability, complex-shaped ceramic parts. Gel casting has been widely studied in the fields of porous materials, composite materials and functional materials, but it is rarely used in actual industrial production because microcracks and deformations often occur in gel casting, resulting in low yields, so it needs to be improved. Summary of the invention

[0004] In order to improve the drying performance of the green body and reduce the occurrence of cracks and deformation, the present application provides a method for preparing a pressureless sintered silicon carbide ceramic large plate by low deformation gel casting.

[0005] The present application provides a method for preparing a large pressureless sintered silicon carbide ceramic plate by gel casting with low deformation, which adopts the following technical scheme:

[0006] A method for preparing a large pressureless sintered silicon carbide ceramic plate by gel casting with low deformation comprises the following steps:

[0007] (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;

[0008] (2) adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry;

[0009] (3) ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain a degassed slurry;

[0010] (4) Adding a catalyst and an initiator to the degassed slurry, stirring and pouring it into a mold, and obtaining a green body after forming and curing. Fixing the green body with a gypsum board and then leaving it to stand for preliminary drying at a constant temperature and humidity;

[0011] (5) After the standing is completed, the gypsum board is removed, and the green body is dried according to the drying system to obtain a dried green body. The dried green body is pressurelessly sintered according to the sintering system to obtain a large silicon carbide ceramic plate.

[0012] By modifying the silicon carbide powder and regulating the slurry components, a silicon carbide ceramic slurry with high solid content and low viscosity is prepared, and the monomer and the cross-linking agent are cross-linked and cured to obtain a high-strength green body. The green body is clamped and fixed with a gypsum board and initially dried at a constant temperature and humidity. The moisture is slowly discharged through the capillary force in the gypsum mold. In this process, the strength of the green body is significantly improved. The high-strength green body helps to resist the drying stress generated during further drying and reduce the occurrence of cracks and deformation.

[0013] Preferably, the monomers in step (1) include acrylamide, sodium alginate oxide and potassium acrylate.

[0014] By using acrylamide, sodium alginate oxide and potassium acrylate as monomers, double cross-linking can be performed through physical and chemical effects to adjust the network structure of the gel, thereby improving the strength of the gel and thus improving the strength of the wet body, and reducing cracking or deformation during the drying process; acrylamide, sodium alginate oxide and potassium acrylate form an interpenetrating cross-linked three-dimensional network with the cross-linking agent through free radical polymerization and ion exchange reaction. The double cross-linked structure can greatly improve the toughness and strength of the gel network, refine the pore size of the network, obtain a denser gel network, increase the network wall thickness, improve the ability to resist drying stress, improve the drying performance of the wet body, and reduce the occurrence of cracking and deformation.

[0015] Preferably, the raw materials for preparing the oxidized sodium alginate include sodium alginate and sodium periodate.

[0016] Sodium periodate can increase the aldehyde structure of sodium alginate, introduce cross-linking points on sodium alginate, improve the reactivity of sodium alginate, enhance the connection of the gel network, and improve the strength and stability of the gel network.

[0017] Preferably, the monomer in step (1) further comprises methylguanamine.

[0018] Methylguanamine can improve the strength of the gel. The amino group in methylguanamine has good reactivity and can undergo cross-linking polymerization inside the gel network to improve the cross-linking degree of the gel network. Methylguanamine can also form stable chemical bonds in the gel network and has a strong physical adsorption effect, which allows the ceramic powder to be evenly dispersed and can improve the stability of the green body. The introduction of methylguanamine can further regulate the pore structure of the gel network, optimize the pore distribution, and promote the effective removal of moisture from the green body, thereby improving the drying performance of the green body and reducing the occurrence of cracks and deformation.

[0019] Preferably, the methylguanamine accounts for 0.1-0.2% of the mass of the slurry.

[0020] By adding methylguanamine according to the above mass content, the obtained green body has high strength and good drying performance.

[0021] Preferably, the raw materials for preparing the modified silicon carbide powder in step (2) include highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine.

[0022] Highly dispersed silicon carbide powder has good dispersibility. It is modified with dimethoxymethylchlorosilane to increase the surface active groups of the highly dispersed silicon carbide powder and improve its reactivity. 2-methyl-1,5-pentanediamine reacts with silane molecules to introduce diamine to the surface of the highly dispersed silicon carbide powder, thereby improving the compatibility and reactivity of the highly dispersed silicon carbide. The amino group can react with the gel network, so that the ceramic powder can be evenly distributed in the gel network, thereby improving the strength of the green body, thereby improving the drying performance and the working performance of the ceramic.

[0023] Preferably, the mass ratio of the highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is 1:0.1:(0.07-0.09).

[0024] The modified silicon carbide powder prepared according to the above mass ratio has good dispersibility and compatibility, and can improve the strength and stability of the green body.

[0025] Preferably, the highly dispersed silicon carbide powder is prepared by the following steps:

[0026] Ultrasonic dispersion of silicon carbide ultrafine powder in deionized water is performed to obtain a silicon carbide dispersion liquid, and a sodium hydroxide aqueous solution is used to adjust the pH of the silicon carbide dispersion liquid to alkaline. Hydroxypropyl distearyl dimethyl ammonium chloride is added to the silicon carbide dispersion liquid after adjusting the pH to obtain a preliminary modified liquid, and the preliminary modified liquid is reacted under stirring conditions in a water bath and then centrifuged, washed with deionized water and dried to obtain highly dispersed silicon carbide.

[0027] The surface of the silicon carbide ultrafine powder is made negatively charged by treatment with sodium hydroxide aqueous solution; Hydroxypropyl distearyl dimethyl ammonium chloride is a gemini quaternary ammonium salt with good positive charge, and can be combined with the silicon carbide ultrafine powder with negative charge on the surface, so that the surface of the silicon carbide ultrafine powder is positively charged, and the dispersion of the powder is improved through steric hindrance and electrostatic repulsion, and the occurrence of agglomeration and sedimentation is reduced; during the sintering process, the gemini quaternary ammonium salt can promote the sintering and viscosity increase of the ceramic powder, and improve the density and strength of the sintered silicon carbide ceramic.

[0028] Preferably, the thickness of the gypsum board in step (4) is 10-15 mm.

[0029] Preferably, the standing condition in step (4) is standing at 55-65% humidity and 28-32° C. for 2.5-3.5 days.

[0030] Carrying out constant temperature and humidity drying treatment under the above conditions can effectively discharge part of the moisture in the blank through the capillary force of the gypsum board, increase the strength of the blank, improve the drying performance of the blank, and reduce the occurrence of cracks and deformation.

[0031] In summary, the present application includes at least one of the following beneficial technical effects:

[0032] 1. Silicon carbide ceramic slurry with high solid content and low viscosity is prepared by modifying silicon carbide powder and regulating the slurry components. The monomer and the cross-linking agent are cross-linked and cured to obtain a high-strength green body. The green body is clamped and fixed with gypsum board and initially dried at constant temperature and humidity. The moisture is slowly discharged through the capillary force in the gypsum mold. In this process, the strength of the green body is significantly improved. The high-strength green body helps to resist the drying stress generated in the further drying process and reduce the occurrence of cracks and deformation.

[0033] 2. Methylguanamine can improve the strength of the gel. The amino group in methylguanamine has good reactivity and can undergo cross-linking polymerization inside the gel network to improve the cross-linking degree of the gel network. Methylguanamine can also form stable chemical bonds in the gel network and has a strong physical adsorption effect, which allows the ceramic powder to be evenly dispersed and can improve the stability of the green body. The introduction of methylguanamine can further regulate the pore structure of the gel network, optimize the pore distribution, and promote the effective removal of moisture from the green body, thereby improving the drying performance of the green body and reducing the occurrence of cracks and deformation.

[0034] 3. Highly dispersed silicon carbide powder has good dispersibility. It is modified with dimethoxymethylchlorosilane to increase the surface active groups of highly dispersed silicon carbide powder and improve its reactivity. 2-methyl-1,5-pentanediamine reacts with silane molecules to introduce diamine to the surface of highly dispersed silicon carbide powder, thereby improving the compatibility and reactivity of highly dispersed silicon carbide. The amino group can react with the gel network, so that the ceramic powder can be evenly distributed in the gel network, thereby improving the strength of the green body, thereby improving the drying performance and the working performance of the ceramic. DETAILED DESCRIPTION

[0035] The present application discloses a method for preparing a large pressureless sintered silicon carbide ceramic plate by gel injection molding with low deformation. The mold used in the present application has a wavy inner frame, and the molding stress is released by curves around the green body to solve the problem of cracking and deformation caused by high stress. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail in combination with the embodiments below:

[0036] Ingredients: Hydroxypropyl distearyl dimethyl ammonium chloride (CAS No.: 118516-73-7), dimethoxymethyl chlorosilane (CAS No.: 994-07-0), 2-methyl-1,5-pentanediamine (CAS No.: 15520-10-2), sodium alginate (CAS No.: 9005-38-3), sodium periodate (CAS No.: 7790-28-5), acrylamide (CAS No.: 79-06-1), potassium acrylate (CAS No.: 10192-85-5), Methylguanamine (CAS No.: 542-02-9), the cross-linking agent is N, N'-methylenebisacrylamide (CAS No.: 110-26-9), the dispersant is CE64, purchased from Qiren Chemical, the suspending agent is sodium carboxymethyl cellulose (CAS No.: 9004-32-4), the defoaming agent is sodium dodecyl sulfate (CAS No.: 151-21-3), the catalyst is tetramethylethylenediamine (CAS No.: 110-18-9), and the initiator is ammonium persulfate (CAS No.: 7727-54-0).

[0037] Example 1

[0038] Preparation of modified silicon carbide powder

[0039] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of deionized water to obtain a silicon carbide dispersion, and the pH of the silicon carbide dispersion was adjusted to 10 using a 1 mol / L sodium hydroxide aqueous solution. 4.5 kg of hydroxypropyl distearyl dimethyl ammonium chloride was added to the silicon carbide dispersion after the pH was adjusted to obtain a preliminary modified liquid. The preliminary modified liquid was stirred at 200 rpm in a 50°C water bath for 3 hours and then centrifuged. After washing with deionized water, it was dried at 80°C to obtain highly dispersed silicon carbide.

[0040] 85.47 kg of highly dispersed silicon carbide powder and 8.55 kg of dimethoxymethylsilyl chloride were mixed and dispersed in 200 mL of toluene, stirred at 200 rpm for 2 h, then 1.1 L of deionized water was added, and the mixture was stirred and reacted at 200 rpm in a water bath at 80 ° C for 4 h, and then 5.98 kg of 2-methyl-1,5-pentanediamine was added. After stirring and reacting at 200 rpm in a water bath at 80 ° C for 4 h, the obtained product solution was filtered, and the obtained solid was washed with anhydrous ethanol. The washed solid was dried in an oven at 80 ° C for 6 h, and the dried solid was ground and passed through a 5000 mesh sieve to obtain modified silicon carbide powder.

[0041] Preparation of oxidized sodium alginate

[0042] Dissolve 2 kg of sodium alginate in 40 L of deionized water at 100° C., cool to obtain a sodium alginate aqueous solution, dissolve 1.8 kg of sodium periodate in 10 L of deionized water to obtain a sodium periodate aqueous solution, add the sodium periodate aqueous solution to the sodium alginate aqueous solution within 2 hours to obtain a sodium alginate reaction solution, react the sodium alginate reaction solution at 30° C. in the dark for 6 hours to obtain a product solution, transfer the product solution to a 3500Da dialysis bag and dialyze for 24 hours, change the water every 8 hours, and freeze-dry the dialyzed product solution at -20° C. to obtain oxidized sodium alginate.

[0043] Preparation of large silicon carbide ceramic plates

[0044] (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;

[0045] (2) Adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, stirring to obtain a slurry; wherein the monomers include acrylamide, sodium alginate oxide, potassium acrylate and methylguanamine, acrylamide accounts for 1.2% of the slurry mass, sodium alginate oxide accounts for 1% of the slurry mass, potassium acrylate accounts for 0.2% of the slurry mass, methylguanamine accounts for 0.1% of the slurry mass, cross-linking agent accounts for 0.2% of the slurry mass, dispersant accounts for 1% of the slurry mass, suspending agent accounts for 0.6% of the slurry mass, defoaming agent accounts for 0.3% of the slurry mass, ceramic powder accounts for 70% of the slurry mass, and the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, and the balance is deionized water.

[0046] (3) The slurry is subjected to ball milling treatment, the ball milling time is 12 hours, the ball milling speed is 30 rpm, and after ball milling, a degassing treatment is performed, vacuum degassing is performed for 10 minutes, and a vibration treatment is performed during degassing, and the vibration frequency is 5 Hz to obtain a degassed slurry;

[0047] (4) Adding a catalyst and an initiator to the deaerated slurry, with the catalyst accounting for 0.005% of the slurry mass and the initiator accounting for 0.005% of the slurry mass, and stirring and pouring into a mold, and obtaining a green body after forming and curing, and fixing the green body with a gypsum board with a thickness of 10 mm, and then standing for 2.5 days at 55% humidity and 32°C for initial drying at constant temperature and humidity;

[0048] (5) After standing, the gypsum board is removed, and the green body is dried according to the drying system in Table 1 to obtain a dried green body. The dried green body is subjected to pressureless sintering, and the temperature is increased to 2100°C at a rate of 8°C / min and kept at this temperature for 2 hours to obtain a large silicon carbide ceramic plate.

[0049] Table 1 Drying system of green body

[0050] Temperature ℃ 30 40 50 50 60 70 90 100 100 70 30 humidity% 75 70 60 50 40 20 0 0 0 0 0 Time 1 20 20 2 10 6 10 5 10 10 4 Example 2

[0051] Preparation of modified silicon carbide powder

[0052] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of deionized water to obtain a silicon carbide dispersion, and the pH of the silicon carbide dispersion was adjusted to 10 using a 1 mol / L sodium hydroxide aqueous solution. 4.5 kg of hydroxypropyl distearyl dimethyl ammonium chloride was added to the silicon carbide dispersion after the pH was adjusted to obtain a preliminary modified liquid. The preliminary modified liquid was stirred at 200 rpm in a 50°C water bath for 3 hours and then centrifuged. After washing with deionized water, it was dried at 80°C to obtain highly dispersed silicon carbide.

[0053] 84.03 kg of highly dispersed silicon carbide powder and 8.41 kg of dimethoxymethylsilyl chloride were mixed and dispersed in 200 mL of toluene, stirred at 200 rpm for 2 h, then 1.1 L of deionized water was added, and the mixture was stirred and reacted at 200 rpm in a water bath at 80 ° C for 4 h, and then 7.56 kg of 2-methyl-1,5-pentanediamine was added. After stirring and reacting at 200 rpm in a water bath at 80 ° C for 4 h, the obtained product solution was filtered, and the obtained solid was washed with anhydrous ethanol. The washed solid was dried in an oven at 80 ° C for 6 h, and the dried solid was ground and passed through a 5000 mesh sieve to obtain modified silicon carbide powder.

[0054] Preparation of oxidized sodium alginate

[0055] Dissolve 2 kg of sodium alginate in 40 L of deionized water at 100° C., cool to obtain a sodium alginate aqueous solution, dissolve 1.8 kg of sodium periodate in 10 L of deionized water to obtain a sodium periodate aqueous solution, add the sodium periodate aqueous solution to the sodium alginate aqueous solution within 2 hours to obtain a sodium alginate reaction solution, react the sodium alginate reaction solution at 30° C. in the dark for 6 hours to obtain a product solution, transfer the product solution to a 3500Da dialysis bag and dialyze for 24 hours, change the water every 8 hours, and freeze-dry the dialyzed product solution at -20° C. to obtain oxidized sodium alginate.

[0056] Preparation of large silicon carbide ceramic plates

[0057] (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;

[0058] (2) Ceramic powders are added to the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirred to obtain a slurry; wherein the monomers include acrylamide, sodium alginate oxide, potassium acrylate and methylguanamine, acrylamide accounts for 1.6% of the slurry mass, sodium alginate oxide accounts for 1.4% of the slurry mass, potassium acrylate accounts for 0.5% of the slurry mass, methylguanamine accounts for 0.2% of the slurry mass, cross-linking agent accounts for 0.3% of the slurry mass, dispersant accounts for 1.2% of the slurry mass, suspending agent accounts for 0.8% of the slurry mass, defoaming agent accounts for 0.5% of the slurry mass, ceramic powder accounts for 68% of the slurry mass, and the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, and the balance is deionized water.

[0059] (3) The slurry is subjected to ball milling treatment, the ball milling time is 16 hours, the ball milling speed is 50 rpm, and after ball milling, it is subjected to degassing treatment, vacuum degassing is performed for 10 minutes, and vibration treatment is performed during degassing, and the vibration frequency is 10 Hz to obtain a degassed slurry;

[0060] (4) Adding a catalyst and an initiator to the deaerated slurry, with the catalyst accounting for 0.01% of the slurry mass and the initiator accounting for 0.01% of the slurry mass, and stirring and pouring into a mold, and obtaining a green body after forming and curing, clamping and fixing the green body with a gypsum board with a thickness of 10 mm, and standing for 3.5 days at 65% humidity and 28°C for initial drying at constant temperature and humidity;

[0061] (5) After standing, the gypsum board is removed, and the green body is dried according to the drying system in Table 1 to obtain a dried green body. The dried green body is subjected to pressureless sintering, and the temperature is increased to 2200°C at a rate of 12°C / min and kept at this temperature for 5 hours to obtain a large silicon carbide ceramic plate.

[0062] Table 1 Drying system of green body

[0063] Temperature ℃ 30 40 50 50 60 70 90 100 100 70 30 humidity% 75 70 60 50 40 20 0 0 0 0 0 Time 1 20 20 2 10 6 10 5 10 10 4 Example 3

[0064] Preparation of modified silicon carbide powder

[0065] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of deionized water to obtain a silicon carbide dispersion, and the pH of the silicon carbide dispersion was adjusted to 10 using a 1 mol / L sodium hydroxide aqueous solution. 4.5 kg of hydroxypropyl distearyl dimethyl ammonium chloride was added to the silicon carbide dispersion after the pH was adjusted to obtain a preliminary modified liquid. The preliminary modified liquid was stirred at 200 rpm in a 50°C water bath for 3 hours and then centrifuged. After washing with deionized water, it was dried at 80°C to obtain highly dispersed silicon carbide.

[0066] 84.75 kg of highly dispersed silicon carbide powder and 8.47 kg of dimethoxymethylsilyl chloride were mixed and dispersed in 200 mL of toluene, stirred at 200 rpm for 2 h, then 1.1 L of deionized water was added, and the mixture was stirred and reacted at 200 rpm in a water bath at 80 ° C for 4 h, and then 6.78 kg of 2-methyl-1,5-pentanediamine was added. After stirring and reacting at 200 rpm in a water bath at 80 ° C for 4 h, the obtained product solution was filtered, and the obtained solid was washed with anhydrous ethanol. The washed solid was dried in an oven at 80 ° C for 6 h, and the dried solid was ground and passed through a 5000 mesh sieve to obtain modified silicon carbide powder.

[0067] Preparation of oxidized sodium alginate

[0068] Dissolve 2 kg of sodium alginate in 40 L of deionized water at 100° C., cool to obtain a sodium alginate aqueous solution, dissolve 1.8 kg of sodium periodate in 10 L of deionized water to obtain a sodium periodate aqueous solution, add the sodium periodate aqueous solution to the sodium alginate aqueous solution within 2 hours to obtain a sodium alginate reaction solution, react the sodium alginate reaction solution at 30° C. in the dark for 6 hours to obtain a product solution, transfer the product solution to a 3500Da dialysis bag and dialyze for 24 hours, change the water every 8 hours, and freeze-dry the dialyzed product solution at -20° C. to obtain oxidized sodium alginate.

[0069] Preparation of large silicon carbide ceramic plates

[0070] (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution;

[0071] (2) Ceramic powders are added to the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirred to obtain a slurry; wherein the monomers include acrylamide, sodium alginate oxide, potassium acrylate and methylguanamine, acrylamide accounts for 1.4% of the slurry mass, sodium alginate oxide accounts for 1.2% of the slurry mass, potassium acrylate accounts for 0.35% of the slurry mass, methylguanamine accounts for 0.15% of the slurry mass, cross-linking agent accounts for 0.25% of the slurry mass, dispersant accounts for 1.1% of the slurry mass, suspending agent accounts for 0.7% of the slurry mass, defoaming agent accounts for 0.4% of the slurry mass, ceramic powder accounts for 69% of the slurry mass, and the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, and the balance is deionized water.

[0072] (3) The slurry was subjected to ball milling treatment, the ball milling time was 14 hours, the ball milling speed was 40 rpm, and after ball milling, degassing treatment was performed, vacuum degassing was performed for 10 minutes, and vibration treatment was performed during degassing, and the vibration frequency was 7.5 Hz to obtain a degassed slurry;

[0073] (4) Adding a catalyst and an initiator to the deaerated slurry, the catalyst accounting for 0.0075% of the slurry mass, and the initiator accounting for 0.0075% of the slurry mass, and stirring and pouring into a mold, and obtaining a green body after forming and curing, and fixing the green body with a gypsum board with a thickness of 10 mm, and then standing for 3 days at 60% humidity and 30°C for initial drying at constant temperature and humidity;

[0074] (5) After standing, the gypsum board is removed, and the green body is dried according to the drying system in Table 1 to obtain a dried green body. The dried green body is subjected to pressureless sintering, and the temperature is increased to 2150°C at a rate of 10°C / min and kept at this temperature for 3.5 hours to obtain a large silicon carbide ceramic plate.

[0075] Table 1 Drying system of green body

[0076] Temperature ℃ 30 40 50 50 60 70 90 100 100 70 30 humidity% 75 70 60 50 40 20 0 0 0 0 0 Time 1 20 20 2 10 6 10 5 10 10 4 Example 4

[0077] Example 4 is based on Example 3, and the only difference between Example 4 and Example 3 is that in Example 4, methylguanamine accounts for 0.05% of the mass of the slurry.

[0078] Example 5

[0079] Example 5 is based on Example 3, and the only difference between Example 5 and Example 3 is that in Example 5, methylguanamine accounts for 0.25% of the mass of the slurry.

[0080] Example 6

[0081] Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of highly dispersed silicon carbide powder used is 86.96 kg, the amount of dimethoxymethylsilyl chloride used is 8.7 kg, and the amount of 2-methyl-1,5-pentanediamine used is 4.34 kg.

[0082] Example 7

[0083] Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of highly dispersed silicon carbide powder used is 81.97 kg, the amount of dimethoxymethylsilyl chloride used is 8.2 kg, and the amount of 2-methyl-1,5-pentanediamine used is 9.83 kg.

[0084] Example 8

[0085] Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, when preparing modified silicon carbide powder, highly dispersed silicon carbide powder is replaced with ultrafine silicon carbide powder.

[0086] Example 9

[0087] Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that dimethoxymethylsilyl chloride is not added when preparing the modified silicon carbide powder in Example 9.

[0088] Example 10

[0089] Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that 2-methyl-1,5-pentanediamine is not added when preparing the modified silicon carbide powder in Example 10.

[0090] Embodiment 11

[0091] Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that the thickness of the gypsum board in step (4) of Example 11 is 5 mm.

[0092] Example 12

[0093] Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that the thickness of the gypsum board in step (4) of Example 12 is 25 mm.

[0094] Example 13

[0095] Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that the standing time in step (4) in Example 13 is 1 day.

[0096] Embodiment 14

[0097] Example 14 is based on Example 3. The only difference between Example 14 and Example 3 is that the standing time in step (4) in Example 14 is 5 days.

[0098] Comparative Example 1

[0099] Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that Comparative Example 1 does not use gypsum board for constant temperature and humidity drying treatment.

[0100] Comparative Example 2

[0101] Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the wavy inner frame mold is replaced by a straight inner frame mold.

[0102] Performance testing

[0103] (1) Density test: The volume and mass of the test sample are measured, and the density is calculated based on the volume and mass. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 2.

[0104] (2) Select GB 16534-2009 Test method for room temperature hardness of fine ceramics as the standard, use a Vickers hardness tester to test, calculate the Vickers hardness of the sample, test each sample three times, take the average value after measurement, and record the results in Table 2.

[0105] (3) Drying performance test: Observe and record the condition of the green body after drying. The results are recorded in Table 2.

[0106] Table 2 Test results of density, hardness and drying performance of silicon carbide ceramic slabs

[0107] Test results <![CDATA[Density (g / cm 3 ).]]> Hardness (GPa) Whether there is crack deformation after drying Example 1 3.15 26 No crack deformation Example 2 3.16 26 No crack deformation Example 3 3.17 27 No crack deformation Example 4 3.14 24 No crack deformation Example 5 3.15 25 No crack deformation Example 6 3.13 23 No crack deformation Example 7 3.15 24 No crack deformation Example 8 3.12 20 There are micro cracks and no deformation Example 9 3.11 19 There are micro cracks and no deformation Example 10 3.12 21 There are micro cracks and no deformation Embodiment 11 3.14 24 No crack deformation Example 12 3.15 25 No crack deformation Embodiment 13 3.13 23 There are micro cracks and no deformation Embodiment 14 3.16 26 No crack deformation Comparative Example 1 3.11 19 There are micro cracks and slight deformation Comparative Example 2 3.13 22 There are micro cracks and slight deformation

[0108] As shown in Table 2, the density of Examples 1-3 is greater than 3.15 g / cm 3 , the hardness is greater than 26GPa, and there is no crack deformation in the green body after drying, which shows that the green body prepared in the present application has good drying performance and strength, and the sintered silicon carbide ceramic large plate has high density and high hardness.

[0109] It can be seen from Table 2 that the only difference between Examples 4 and 5 and Example 3 is that in Example 4, methylguanamine accounts for 0.05% of the mass of the slurry, and in Example 5, methylguanamine accounts for 0.25% of the mass of the slurry. Compared with Example 3, the density and hardness of Examples 4 and 5 are reduced. This is because the amount of methylguanamine is changed. Too much or too little methylguanamine will affect the crosslinking degree and pore structure of the gel network, thereby affecting the discharge of water during drying, reducing the drying performance, and further affecting the performance of the ceramic slab after sintering.

[0110] As can be seen from Table 2, the only difference between Examples 6 and 7 and Example 3 is that in Example 6, the mass ratio of highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is 1:0.1:0.05, and in Example 7, the mass ratio of highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is 1:0.1:0.12. Compared with Example 3, the density and hardness of Examples 6 and 7 are reduced; this is because the mass ratio of highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is not within the specified range, which affects the dispersibility and compatibility of the modified silicon carbide powder, reduces the uniformity of the ceramic powder in the gel network, thereby reducing the strength and drying performance of the green body, and further affecting the hardness and density of the ceramic slab.

[0111] As can be seen from Table 2, the only difference between Examples 8, 9, and 10 and Example 3 is that in Example 8, the highly dispersed silicon carbide powder is replaced with silicon carbide ultrafine powder when preparing the modified silicon carbide powder, and in Example 9, dimethoxymethylchlorosilane is not added when preparing the modified silicon carbide powder. In Example 10, 2-methyl-1,5-pentanediamine is not added when preparing the modified silicon carbide powder. Compared with Example 3, in Examples 8, 9, and 10, the drying performance and strength of the green body are reduced, and the density and hardness of the ceramic slab are reduced; this is because the preparation components of the modified silicon carbide powder are replaced, the highly dispersed silicon carbide powder is replaced with silicon carbide ultrafine powder, and there is a lack of dispersion modification treatment, and the silicon carbide ultrafine powder is prone to agglomeration during silane modification; if silane is not added to modify the powder, the reaction sites on the powder surface are reduced, and the modification effect of diamine is reduced; if diamine is not added, the reactivity of the powder with the gel network is reduced, the strength and drying performance of the green body are reduced, and thus the density and hardness are reduced.

[0112] As can be seen from Table 2, the only difference between Examples 11, 12, 13, and 14 and Example 3 is that the thickness of the gypsum board in step (4) of Example 11 is 5 mm, the thickness of the gypsum board in step (4) of Example 12 is 25 mm, the standing time in step (4) of Example 13 is 1 day, and the standing time in step (4) of Example 14 is 5 days. Compared with Example 3, the density and hardness of Examples 11, 12, 13, and 14 are reduced, and the drying effect is slightly reduced. This is because the thickness of the gypsum board will affect the removal of moisture. Too thin or too thick will affect the drying effect. The drying time will affect the amount of moisture removed. If the time is too short, the moisture removed by capillary force is limited, and the moisture content of the green body is still high in the subsequent drying process, thereby affecting the drying effect and the strength of the green body, and further affecting the density and hardness.

[0113] It can be seen from Table 2 that the only difference between Comparative Example 1 and Example 3 is that Comparative Example 1 does not use gypsum board for constant temperature and humidity drying treatment. Compared with Example 3, the drying effect and strength of Comparative Example 1 are reduced, and the density and hardness are reduced; this is because without constant temperature and humidity drying treatment, part of the moisture cannot be removed by capillary force to improve the strength of the green body. In the subsequent drying process, the green body is prone to cracks and deformation, which in turn affects the density and hardness.

[0114] It can be seen from Table 2 that the only difference between Comparative Example 2 and Example 3 is that Comparative Example 2 replaces the wavy inner frame mold with a straight inner frame mold. Compared with Example 3, Comparative Example 2 has reduced density and hardness, and the drying effect is worse; this is because when the frame is a straight line, there is a lack of curves to release stress, and the blank is prone to deformation and cracking under the action of internal stress, which in turn affects the drying performance and the performance of the ceramic slab, and the density and hardness are reduced.

[0115] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing a large pressureless sintered silicon carbide ceramic plate by gel casting with low deformation, characterized in that: The steps include: (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution; (2) adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry; (3) ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain a degassed slurry; (4) Adding a catalyst and an initiator to the degassed slurry, stirring and pouring it into a mold, and obtaining a green body after forming and curing. Fixing the green body with a gypsum board and then leaving it to stand for preliminary drying at a constant temperature and humidity; (5) After the standing is completed, the gypsum board is removed, and the green body is dried according to the drying system to obtain a dried green body, and the dried green body is pressurelessly sintered according to the sintering system to obtain a large silicon carbide ceramic plate; The monomers in step (1) include acrylamide, sodium alginate oxide and potassium acrylate; The monomer in step (1) further comprises methylguanamine; The raw materials for preparing the oxidized sodium alginate include sodium alginate and sodium periodate; The acrylamide accounts for 1.2% of the slurry by mass, the oxidized sodium alginate accounts for 1% of the slurry by mass, the potassium acrylate accounts for 0.2% of the slurry by mass, the methylguanamine accounts for 0.1% of the slurry by mass, the cross-linking agent accounts for 0.2% of the slurry by mass, the dispersant accounts for 1% of the slurry by mass, the suspending agent accounts for 0.6% of the slurry by mass, the defoaming agent accounts for 0.3% of the slurry by mass, the ceramic powder accounts for 70% of the slurry by mass, and the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, and the balance is deionized water; The raw materials for preparing the modified silicon carbide powder in step (2) include highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine; The mass ratio of the highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is 1:0.1:(0.07-0.09); The highly dispersed silicon carbide powder is prepared by the following steps: Ultrasonic dispersion of silicon carbide ultrafine powder in deionized water to obtain a silicon carbide dispersion liquid, adjusting the pH of the silicon carbide dispersion liquid to alkaline using an aqueous sodium hydroxide solution, adding hydroxypropyl distearyl dimethyl ammonium chloride to the silicon carbide dispersion liquid after adjusting the pH to obtain a preliminary modified liquid, reacting the preliminary modified liquid under stirring in a water bath, centrifuging it, washing it with deionized water, and drying it to obtain highly dispersed silicon carbide; The thickness of the gypsum board in step (4) is 10-15 mm; The standing condition in step (4) is to stand at 55-65% humidity and 28-32° C. for 2.5-3.5 days.

2. A method for preparing a large pressureless sintered silicon carbide ceramic plate by gel casting with low deformation, characterized in that: The steps include: (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution; (2) adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry; (3) ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain a degassed slurry; (4) Adding a catalyst and an initiator to the degassed slurry, stirring and pouring it into a mold, and obtaining a green body after forming and curing. Fixing the green body with a gypsum board and then leaving it to stand for preliminary drying at a constant temperature and humidity; (5) After the standing is completed, the gypsum board is removed, and the green body is dried according to the drying system to obtain a dried green body, and the dried green body is pressurelessly sintered according to the sintering system to obtain a large silicon carbide ceramic plate; The monomers in step (1) include acrylamide, sodium alginate oxide and potassium acrylate; The monomer in step (1) further comprises methylguanamine; The raw materials for preparing the oxidized sodium alginate include sodium alginate and sodium periodate; The acrylamide accounts for 1.6% of the mass of the slurry, the oxidized sodium alginate accounts for 1.4% of the mass of the slurry, the potassium acrylate accounts for 0.5% of the mass of the slurry, the methylguanamine accounts for 0.2% of the mass of the slurry, the cross-linking agent accounts for 0.3% of the mass of the slurry, the dispersant accounts for 1.2% of the mass of the slurry, the suspending agent accounts for 0.8% of the mass of the slurry, the defoaming agent accounts for 0.5% of the mass of the slurry, the ceramic powder accounts for 68% of the mass of the slurry, and the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, and the balance is deionized water; The raw materials for preparing the modified silicon carbide powder in step (2) include highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine; The mass ratio of the highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is 1:0.1:(0.07-0.09); The highly dispersed silicon carbide powder is prepared by the following steps: Ultrasonic dispersion of silicon carbide ultrafine powder in deionized water to obtain a silicon carbide dispersion liquid, adjusting the pH of the silicon carbide dispersion liquid to alkaline using an aqueous sodium hydroxide solution, adding hydroxypropyl distearyl dimethyl ammonium chloride to the silicon carbide dispersion liquid after adjusting the pH to obtain a preliminary modified liquid, reacting the preliminary modified liquid under stirring in a water bath, centrifuging it, washing it with deionized water, and drying it to obtain highly dispersed silicon carbide; The thickness of the gypsum board in step (4) is 10-15 mm; The standing condition in step (4) is to stand at 55-65% humidity and 28-32° C. for 2.5-3.5 days.

3. A method for preparing a large pressureless sintered silicon carbide ceramic plate by gel casting with low deformation, characterized in that: The steps include: (1) Mix the monomer, cross-linking agent, deionized water, dispersant, suspending agent and defoaming agent and stir them thoroughly to obtain a premixed solution; (2) adding ceramic powders into the premixed liquid in the order of boron carbide, carbon black and modified silicon carbide powder, and stirring to obtain a slurry; (3) ball milling the slurry, degassing the slurry after ball milling, and vibrating the slurry during degassing to obtain a degassed slurry; (4) Adding a catalyst and an initiator to the degassed slurry, stirring and pouring it into a mold, and obtaining a green body after forming and curing. Fixing the green body with a gypsum board and then leaving it to stand for preliminary drying at a constant temperature and humidity; (5) After the standing is completed, the gypsum board is removed, and the green body is dried according to the drying system to obtain a dried green body, and the dried green body is pressurelessly sintered according to the sintering system to obtain a large silicon carbide ceramic plate; The monomers in step (1) include acrylamide, sodium alginate oxide and potassium acrylate; The monomer in step (1) further comprises methylguanamine; The raw materials for preparing the oxidized sodium alginate include sodium alginate and sodium periodate; The acrylamide accounts for 1.4% of the slurry by mass, the oxidized sodium alginate accounts for 1.2% of the slurry by mass, the potassium acrylate accounts for 0.35% of the slurry by mass, the methylguanamine accounts for 0.15% of the slurry by mass, the cross-linking agent accounts for 0.25% of the slurry by mass, the dispersant accounts for 1.1% of the slurry by mass, the suspending agent accounts for 0.7% of the slurry by mass, the defoaming agent accounts for 0.4% of the slurry by mass, the ceramic powder accounts for 69% of the slurry by mass, and the mass ratio of boron carbide, carbon black and modified silicon carbide powder in the ceramic powder is 0.6:2:97.4, and the balance is deionized water; The raw materials for preparing the modified silicon carbide powder in step (2) include highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine; The mass ratio of the highly dispersed silicon carbide powder, dimethoxymethylchlorosilane and 2-methyl-1,5-pentanediamine is 1:0.1:(0.07-0.09); The highly dispersed silicon carbide powder is prepared by the following steps: Ultrasonic dispersion of silicon carbide ultrafine powder in deionized water to obtain a silicon carbide dispersion liquid, adjusting the pH of the silicon carbide dispersion liquid to alkaline using an aqueous sodium hydroxide solution, adding hydroxypropyl distearyl dimethyl ammonium chloride to the silicon carbide dispersion liquid after adjusting the pH to obtain a preliminary modified liquid, reacting the preliminary modified liquid under stirring in a water bath, centrifuging it, washing it with deionized water, and drying it to obtain highly dispersed silicon carbide; The thickness of the gypsum board in step (4) is 10-15 mm; The standing condition in step (4) is to stand at 55-65% humidity and 28-32° C. for 2.5-3.5 days.